ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI TERAPI KOMPLEMENTER DEEP BREATHING EXERCISE DAN SLOW STROKE BACK MASSAGE TERHADAP NYERI AKUT PADA PASIEN DENGAN CONGESTIVE HEART FAILURE (CHF) DI RUANG CEMARA 1 RS BHAYANGKARA TINGKAT I RADEN SAID SUKANTO - Ganis Eka Madani (2022)
Congestive heart failure patients usually complain of shortness of breath at night to orthopnea, extremities edema, and discomfort in the abdominal area, especially in the right-upper quadrant. As a result of this pain, there is an increase in sympathetic activation so it has an impact on increasing the work of the heart and contributing to worsening the symptoms of CHF. Epigastric pain or heartburn in CHF is caused by passive congestion effect from portal stasis and resulting in hemodynamic disturbances in the splanchnic circulation. Nurses play a role in non-pharmacological pain management for CHF patients by providing complementary therapies. Complementary therapies applied in this study are deep breathing exercises and slow stroke back massage. This scientific work aims to analyze the effectiveness of DBE and SSBM therapy for acute pain in CHF patients in Cemara 1 Hospital Bhayangkara Level I Raden Said Sukanto. After the DBE and SSBM interventions were carried out for three days once per day in 15-20 minutes, the acute pain problems could be resolved in first patients, while the second patients only experienced a decrease in the pain scale. Differences changes in pain intensity between patients are caused by: 1) physiological factors in the form of differences in clinical conditions that affect the effectiveness of therapy; 2) psychosocial factors, namely the patient's perception and tolerance of the pain he feels.